URGENSI KOMUNIKASI INTERPERSONAL DALAM MEWUJUDKAN KELUARGA SAKINAH: STUDI TENTANG PERAN KOMUNIKASI SUAMI ISTRI DALAM PENYELESAIAN KONFLIK RUMAH TANGGA - Rani Farida; Wahyudi; Raya Rambu Rabbani (Jurnal Keluarga Sehat Sejahtera, 2025)
This study examines the urgency of interpersonal communication between husbands and wives in creating a sakinah family, which is a harmonious family, full of love and spiritual peace as recommended in Islamic teachings. Using a qualitative approach based on literature review, this study examines various theories and scientific perspectives on the dynamics of communication in marital relationships. The results show that effective interpersonal communication based on openness, empathy, honesty, and spiritual values is the key to resolving domestic conflicts and strengthening emotional bonds. This study also highlights the importance of assertive communication strategies, quality time, and active listening techniques as constructive ways to build healthy relationships that can withstand the dynamics of differences. Poor communication has the potential to create conflict and reduce the quality of marriage, while healthy communication can be a means of fostering a family that is whole, stable, and in line with the ideals of sakinah mawaddah wa rahmah. These findings are expected to contribute to the development of Islamic family law studies and marriage counseling in the context of Indonesian religious society.